1999
DOI: 10.1007/s004140050245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol on body-sway patterns in human subjects

Abstract: The vestibulospinal aspects of vestibular function are commonly neglected in the evaluation of alcohol-induced intoxication. Thus, in the present study the effect of an acute intoxication with a low or moderate quantity of alcohol was examined with respect to the equilibrium in 30 healthy subjects. The blood alcohol concentration (BAC) was measured 30 min after the ingestion of the last alcohol, ranging between 0.22 and 1.59 per thousand. Stability of stance was quantified by static platform posturography in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 31 publications
4
41
1
2
Order By: Relevance
“…During unperturbed standing, the stability was only marginally affected at 0.06% BAC, whereas under balance perturbations the body movement increases were almost linearly related to the increase in BAC and the stability was substantially deteriorated already at 0.06% BAC. In accordance with our findings, previous studies have revealed that the unperturbed standing is only marginally impaired by alcohol intoxication below 0.08% BAC (Nieschalk et al, 1999). Hence, while a subject with 0.06% BAC may find the quiet stance stability almost unaffected, the subject may find a balance perturbation unexpectedly already difficult to handle at 0.06% BAC.…”
Section: Lateral P1/p4supporting
confidence: 91%
See 2 more Smart Citations
“…During unperturbed standing, the stability was only marginally affected at 0.06% BAC, whereas under balance perturbations the body movement increases were almost linearly related to the increase in BAC and the stability was substantially deteriorated already at 0.06% BAC. In accordance with our findings, previous studies have revealed that the unperturbed standing is only marginally impaired by alcohol intoxication below 0.08% BAC (Nieschalk et al, 1999). Hence, while a subject with 0.06% BAC may find the quiet stance stability almost unaffected, the subject may find a balance perturbation unexpectedly already difficult to handle at 0.06% BAC.…”
Section: Lateral P1/p4supporting
confidence: 91%
“…These have revealed that BAC above 0.07% -0.08% impairs postural control in unperturbed standing (Dick et al, 1989;Nieschalk et al, 1999;Thyssen et al, 1981), whereas perturbed standing can be affected from about 0.06% BAC (Woollacott, 1983). However, most studies performed on human postural control and alcohol intoxication were done over 20 years ago.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute alcohol intoxication temporarily affects cerebellar function (Chu, 1983), producing symptoms that resemble mild or moderate cerebellar ataxia (Diener et al, 1983;Nieschalk et al, 1999), including loss of coordination between eye movements and other visually guided actions (Crowdy and Marple-Horvat, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This output implies that alcohol has a particular influence on control over static posture, which is closely related to instability of the ankle, and this seems to result from a decrease in reaction velocity of nerve roots 12) . A study by Nieschalk found that measuring postural stability by using Romberg's test after applying a small and middle amount of alcohol showed that the tests with the eyes open and closed revealed a relation between the blood alcohol content and postural sway 13) . Another study measured the velocity and range of postural sway after injecting alcohol by 0.5 mL/kg of alcohol 14) .…”
Section: Discussionmentioning
confidence: 99%